2013
DOI: 10.1186/2051-1426-1-s1-p248
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of circulating myeloid derived suppressor cells and dendritic cells in Egyptian patients with chronic Hepatitis C Virus infection undergoing treatment with IFN-α-based therapy

Abstract: Salem et al.: Frequencies of circulating myeloid derived suppressor cells and dendritic cells in Egyptian patients with chronic Hepatitis C Virus infection undergoing treatment with IFN-αbased therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Second, viral infections could induce proinflammatory mediators as cytokines (IL‐1 family members, IL‐6, TNF, and IL‐10), lipid mediators (prostaglandin E2 [PGE2]), and growth factors (GM‐CSF), leading to generation of MDSC by enhancing myelopoiesis, skewing differentiation of progenitors into monocytes and DCs (STAT3/STAT5 activation), and promoting survival of M‐MDSC . Moreover, previous studies reported that MDSC confer unfavorable effects on the protective immune responses in patients with chronic HCV infection and their level decreases after successful interferon therapy …”
Section: Discussionmentioning
confidence: 99%
“…Second, viral infections could induce proinflammatory mediators as cytokines (IL‐1 family members, IL‐6, TNF, and IL‐10), lipid mediators (prostaglandin E2 [PGE2]), and growth factors (GM‐CSF), leading to generation of MDSC by enhancing myelopoiesis, skewing differentiation of progenitors into monocytes and DCs (STAT3/STAT5 activation), and promoting survival of M‐MDSC . Moreover, previous studies reported that MDSC confer unfavorable effects on the protective immune responses in patients with chronic HCV infection and their level decreases after successful interferon therapy …”
Section: Discussionmentioning
confidence: 99%
“…Increased MDSC frequencies positively correlate with HCV viral load and decreased CD8 T-cell function ( 21 , 99 ). Reports show that elevated levels of immature Lin − HLA-DR − CD33 + CD11b + MDSC, consisting of M-MDSC and PMN-MDSC, in chronic HCV-infected patients, decline following successful IFN-α treatment ( 98 ), while treatment-naive HCV-infected individuals show significantly increased liver- and circulating MDSC frequencies compared to treated and uninfected individuals ( 99 , 161 ). Nonetheless, other in vivo investigations failed to show significant MDSC elevations or an association with viral load ( 100 ).…”
Section: M-mdsc In Pathophysiology Of Chronic Infectionsmentioning
confidence: 99%
“…We and others have reported that chronic HCV patients harbor high numbers of MDSCs in nonresponders than in responders (Grutzner et al, 2016;Younis et al, 2016;Salem et al, 2017). The responders have the tendency of lower MDSC levels than non-responders (Salem et al, 2013).…”
Section: Introductionmentioning
confidence: 70%